MODERN CLINICAL AND MORPHOLOGICAL APPROACHES TO THE TREATMENT OF STOMACH CANCER AT AN EARLY STAGE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article presents the results of histological examination of early gastric cancer removed by endoscopic submucosal dissection. The algorithm of morphological research is given: methods of histological, histochemical and immunohistochemical processing of tissue samples, the sequence of morphological analysis with the conclusion and conclusions about the effectiveness of endoscopic surgery is analyzed.